Extraction of matrine from Sophora flavescens Ait. and evaluation of its inhibitory effects on human nasopharyngeal carcinoma CNE-2 cells - WANG,Ming (2018)
Abstract The present study investigated the extraction and purification technology of matrine from Sophora flavescens Ait. and the inhibitory effects of matrine on human nasopharyngeal carcinoma (NPC) CNE-2 cells. The matrine was extracted from Sophora flavescens Ait. by decocting using ethanol-aqueous solution as the solvent, followed by purification using ion exchange resin adsorption. The extraction and purification conditions were investigated. The effects of matrine on growth, cell apoptosis and cycle of CNE-2 cells and expressions of Bac-2 and caspase-3 protein in cells were detected. Results showed that, the optimal extraction and purification technologies of matrine from Sophora flavescens Ait. were obtained, under which the purity of matrine was 81.56%. Matrine could obtain inhibit the growth of CNE-2 cells, promote the cell apoptosis, and arrest most cells in G0/G1 phase. In addition, after treated matrine, the relative expression level of Bcl-2 protein in CNE-2 cells was decreased, and the expression level of Caspase-3 protein was increased. In conclusion, matrine has inhibitory effects on human NPC CNE-2 cells. The mechanism may be related to its down-regulation of Bcl-2 protein and up-regulation of Caspase-3 protein expression.